La reflexión en la formación inicial del profesorado: una mirada desde las experiencias en la asignatura Ambientes de aprendizaje para el desarrollo del pensamiento lógico matemático - Rodriguez Rodriguez, Diana Isabel (2021)
This research aims to socialize the reflections generated from the design and application of resources and activities developed in the subject Learning environments for the development of mathematical logical thinking, in the Initial Education career of the National University of Education. The work constitutes an investigation with a qualitative approach, which seeks to give meaning to the actions of teachers in training, as a result of the experience in real learning scenarios. It highlights the main contributions of teachers in training on the essential factors to develop meaningful experiences in virtuality and their self-reflection on what is implemented in the learning process. The results reflect that, in effect, as an active part of the practice, the teacher in training generates self-criticism processes aimed at the continuous improvement of their actions, which significantly influences their training process.